Geographic distribution and regional origin of 272 cystic fibrosis mutations in European populations. The Biomed CF Mutation Analysis Consortium - Estivill, Xavier; Bancells, Consol; Ramos, Cristina; Macek, Milan; Macek, Milan; Krebsová, Alice; Vávrová, Věra (Human mutation, 1997)
The geographic distribution of 272 cystic fibrosis (CF) mutations has been studied by assessing the origin of 27,177 CF chromosomes from 29 European countries and three countries from the North of Africa. The most common mutations are delta F308 (66.8%), G542X (2.6%), N1303K (1.6%), G551D (1.5%) and W1282X (1.0%). The delta F508 mutation has the highest frequency in Denmark (87.2%) and the lowest in Algeria (26.3%). Mutation G542X is common in the Mediterranean countries, with a mean frequency of 6.1%. N1303K is found in most of the western and Mediterranean countries and has the highest frequency in Tunisia (17.2%). The wide distribution of these mutations suggests an ancient origin. G551D is common in north-west and central Europe, but is uncommon in other parts of Europe. W1282X has the highest frequency in Israel (36.2%), being also common in most Mediterranean countries and north Africa. Seventeen mutation have frequencies between 0.1 and 0.9%, 1717-1G-->A (0.83%), R553X (0.75%), R1162X (0.51%), 621 + 1G-->T (0.54%) and 2183AA-->G (0.36%), being the most common ones. Some mutations reach relatively high frequencies in some extended geographic regions, such as mutation 394delTT in northern Europe (1.1-28.8%), R117H in northwestern Europe (1.3-3.0%), R553X in central Europe (1.1-24.4%), 1717-1G-->A in Belgium and France (1.1-5.3%), and 2183AA-->G in Italy and Greece (3.2%). Other mutations are only common in small regions: T338I (Sardinia), 711 + 1G-->T (Tunisia), R1162X (Algeria and north of Italy), 1609delCA (east of Spain), 1811 + 1.6kbA-->G (southeastern Spain), R1066C (Portugal), S549R (Algeria), R334W (Crete), 621 + 1G-->T (Central Greece), 3849 + 10kbC-->T (Israel), 2789 + 5G-->A (south of Greece), 451 + 1G--A (Israel), R347P (south of Bulgaria), 1677delTA (south of Bulgaria and Turkey), G85E (south of Greece), R347H (Turkey), 3905insT (Switzerland), 1078delT (Brittany), 1898 + 1G-->A (Wales), A455E (The Netherlands), delta I507 (Brittany), 3659delC (Sweden) and R560T (northern Ireland). Most of these mutations must have an origin and diffusion in the specific European population subgroup. Overall 55 mutations are common in one or several countries or regions of Europe and 217 mutations are rare with relative frequencies of lower than 1% in any of these regions and countries. This information might facilitate mutation analysis of CF in the different regions of Europe.
Keywords: mutace; frekvence genu; Genetic Variation; heterozygot; cystická fibróza; Gene Frequency; lidé; Genetics, Population; Heterozygote; Europe; Evropa; severní Afrika; Mutation; genetická variace; Africa, Northern; Cystic Fibrosis; populační genetika; Humans